Economic, Environmental, and Social Evaluation of Africa's Small-Scale Fisheries - World Bank (Washington, DC, 2015)
This report is the culmination of a cross-African countries analytical and empirical study commissioned by the World Bank, which set out to improve the understanding of the characteristics and environmental, economic, and social performances of small-scale fisheries in Africa. It applies a common evaluation tool, called Fishery Performance Indicators (FPIs), which evaluates the ecological, social, and economic performances of a particular fishery. This paper is a compilation of a series of case studies to cast some light on the status of SSFs in Africa. The fisheries case studies range from inland to marine, single to multispecies, East to West African, and from artisanal to semi-industrial fisheries. A template was developed to provide structure and guidance for these case studies. Each case study involved the following elements: (a) characterization of SSFs (at both the national and case-study levels); (b) legal and institutional framework for case-study countries and communities; and (c) social, economic, and environmental performance of case-study fisheries. This synthesis report focuses on element (c) by using the standard Fishery Performance Indicators (FPIs) to do the comparison analysis. This report uses the quantitative results from the FPIs to explore commonalities and differences among and between the nine African fisheries in six countries (Ghana, Kenya, Liberia, Malawi, Senegal, and Sierra Leone) and to infer their relative strengths and weaknesses. Overall, there are large performance gaps in the recent African SSFs in terms of the output performance. These fisheries have unhealthy fish stock, high-risk volatility, weak market performance, and postharvest performance.